2015
DOI: 10.1590/0104-4060.43236
|View full text |Cite
|
Sign up to set email alerts
|

Análise sobre variáveis explicativas da autoeficácia docente

Abstract: RESUMOEsta pesquisa teve como objetivo analisar as possíveis relações explicativas entre variáveis pessoais, variáveis de atividade docente e variáveis contextuais e as crenças de autoeficácia docente de professores do ensino médio público paulista. Tal crença é entendida como o julgamento que o professor faz acerca de suas próprias capacidades para atingir resultados desejados de engajamento e aprendizagem dos alunos, mesmo entre aqueles que podem ser difíceis ou desmotivados, e tem sido associada à satisfaçã… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 17 publications
(24 reference statements)
0
0
0
Order By: Relevance
“…The teachers' conception of students' potential to learn a given content is mediated by the beliefs of teacher self-efficacy, which, in turn, favor the students' learning context (Casanova & Azzi, 2015). Thus, the intervention, by strengthening the teachers' self-efficacy beliefs, may have favored the reflection on their ways of thinking and acting in the school routine, contributing to critical decision-making in face of their instructional and sociability practices.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The teachers' conception of students' potential to learn a given content is mediated by the beliefs of teacher self-efficacy, which, in turn, favor the students' learning context (Casanova & Azzi, 2015). Thus, the intervention, by strengthening the teachers' self-efficacy beliefs, may have favored the reflection on their ways of thinking and acting in the school routine, contributing to critical decision-making in face of their instructional and sociability practices.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the teachers' self-efficacy beliefs positively influence the selection of appropriate and innovative teaching strategies, the establishment of goals, and the consistency of teachers in the pursuit of objectives, contributing to the motivation, academic performance, and well-being of their students (Bandura, 1997;Casanova & Azzi, 2015;Fackler & Malmberg, 2016). Thus, it is observed that teachers with self-efficacy beliefs manage adversities better, adapt more easily to changes, (whether curricular or structural), becoming more engaged, persistent, and committed to more effective classroom strategies (Rodrigues & Iaochite, 2018).…”
mentioning
confidence: 99%